Effects of Maternal Nutrition on Female Offspring Weight Gain and Sexual Development - Cracco, Roberta Cavalcante; Bussiman, Fernando de Oliveira; Polizel, Guilherme Henrique Gebim; Furlan, Édison; Garcia, Nara Pontes; Poit, Diego Angelo Schmidt; Pugliesi, Guilherme; Santana, Miguel Henrique de Almeida (Frontiers in Genetics, 2021)
Maternal nutrition during pregnancy influences postnatal life of animals; nevertheless, few studies have investigated its effects on the productive performance and reproductive development of heifers. This study evaluated the performance, reproductive development, and correlation between reproduction x fat thickness and performance x ribeye area (REA) traits of heifers. We also performed an exploratory genomic association during the rearing period in heifers submitted to fetal programming. The study comprised 55 Nellore heifers, whose mothers received three nutritional plans: Control, without protein-energy supplementation; PELT – Protein-energy last trimester, protein-energy supplementation offered in the final third of pregnancy; and PE - Full Programmed, protein-energy supplementation upon pregnancy confirmation. Protein-energy supplementation occurred at the level of 0.3% live weight. After weaning, heifers were submitted to periodic evaluations of weight and body composition by ultrasonography. From 12 to 18 months, we evaluated the reproductive tract of heifers to monitor its development for sexual precocity and ovarian follicle population. The treatments had no effect (p > 0.05) on average daily gain; however, the weight of the animals showed a significant difference over time (p = 0.017). No differences were found between treatments for ribeye area, backfat and rump fat thickness, nor for puberty age, antral follicular count, and other traits related to reproductive tract development (p > 0.05). The correlation analysis between performance traits and REA showed high correlations (r > 0.37) between REA at weaning and year versus weight from weaning until yearling; however, no correlation was found for reproductive development traits versus fat thickness (p > 0.05). The exploratory genomic association study showed one SNP for each treatment on an intergenic region for control and PEWG, and the one for PELT on an intronic region of RAPGEF1 gene. Fetal programming affected only the weight of the animals throughout the rearing period.